Estabelecimento e caracterização de um modelo in vivo e in vitro de mixoma odontogênico - Juliana Cristina de Souza (2021)
Odontogenic myxoma (OM) is a rare intraosseous neoplasm. Despite being benign, OM has an aggressive behavior and is locally infiltrative, which can cause facial deformities and impact patient’s quality of life. In addition, although many studies have been carried out, the pathogenesis of this tumor has not yet been fully elucidated. Conservative surgical treatments are associated with an increased probability of recurrences. Collectively, all these facts make new therapies options necessary. The MAPK/ERK pathway regulates cellular processes such as cell proliferation, differentiation and survival and it is constitutively activated in several neoplasms, including those of odontogenic origin. Thus, we aimed to assess whether this pathway is activated in OM samples; for this purpose, immunohistochemistry reactions were performed for pERK1/2. As all samples evaluated showed strong pERK1/2 immunoexpression, it was proposed to stablish a 3D organotypic culture model and a patient-derived xenograft model for OM to test the effects of MAPK/ERK pathway inhibition by means of the MEK inhibitor, U0126. There was a decrease in perk1/2/ERK1/2 fold-change in samples in vitro treated with MEK inhibitor U0126, indicating that occurred the inhibition of MAPK pathway activation. Consistent with the cell culture results, there was a shrinkage of the tumor volume in the in vivo model treated with U0126 when compared to the control group. The histology of the primary tumor was maintained in the treated and untreated OM samples that were used to establish both models. The tumors maintained in the PDX model showed, microscopically, the presence of blood capillaries between neoplastic cells. Then, it was hypothesized that they were derived from the mouse used in the PDX model, as, macroscopically, an increase in vascularization around the OM fragments was observed. However, immunohistochemistry reactions for the major histocompatibility complex class 1 (MHC 1) of human (HLA ABC) and mouse (H2Db) showed immunoexpression only for the patient’s MHC 1. In conclusion, the in vitro and in vivo models established are good models for the study of OM, as they demonstrate good reproducibility of the primary features of the tumor and, the results obtained are promising for a preclinical frame for OM-targeted therapy.